Bariatric Surgery in Adults with Obesity: the Impact on Performance, Metabolism, and Health Indices - Georges Jabbour (754884) (2022)
This systematic review summarizes current evidence on the impact of bariatric surgery (BS) on physical performance, metabolic, and health indices in adults with obesity. This systematic review suggests that BS induced significant reductions in body weight, fat mass, and fat-free mass in individuals with obesity. Additionally, BS may improve many physical fitness and health indicators. Observed improvements manifest during a distinct period of time. To date, studies on BS and performance have been small in number, nonrandomized in design, and not controlled regarding gender distribution and/or post-surgery follow-up. Future studies should further investigate concerns associated with understanding of BS outcomes to improve these outcomes with potential benefits for quality of life, disability, mortality, morbidity, and overall BS success. Other Information Published in: Obesity Surgery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11695-020-05182-z